A high stellar multiplicity rate amongst TESS planet candidates in the Neptunian desert using Gaia DR3 astrometry - Eeles-Nolle, Fintan; Armstrong, David J (Monthly notices of the Royal Astronomical Society, 2025)
We aim to discover whether the stellar multiplicity rate may provide information on the origin of recently discovered planets in the Neptunian desert. Using Gaia Data Release 3 astrometry, we search for common proper motion companions to 1779 known exoplanet hosts and 2927 exoplanet candidate hosts from the Transiting Exoplanet Survey Satellite (TESS) mission, both within 650 pc. We find overall stellar multiplicity rates of $16.6± 0.9 {{\, \rm per\, cent}}$ and $19.8± 0.6 {{\, \rm per\, cent}}$ for confirmed and candidate exoplanets, respectively. We find stellar multiplicity rates of $16.7± 5.8 {{\, \rm per\, cent}}$ and $27.5± 2.6 {{\, \rm per\, cent}}$ for confirmed and candidate exoplanets in the Neptunian desert, respectively. Hot Jupiter host stars were found to have rates of $25.8± 2.1 {{\, \rm per\, cent}}$ and $22.9± 1.3 {{\, \rm per\, cent}}$. For the sample of candidate exoplanets, we find higher stellar multiplicity rates for stars hosting both hot Jupiters and Neptunian desert planets compared to control samples of similar stars not known to host planets. For the sample of confirmed exoplanets, an increased multiplicity rate is seen for hot Jupiter hosts, but cannot be significantly determined for Neptunian desert planet hosts due to small sample sizes. If the candidates from TESS are indeed planets, the increased multiplicity rate observed could indicate that the Neptunian desert and hot Jupiter populations share similar formation mechanisms and environmental conditions. Alternatively, the TESS candidate high multiplicity rate could imply a prevalence of false positives related to binary and triple stars in this parameter space.